A newborn infant with intrapericardial rhabdomyosarcoma: a case report - Tutak, Ercan; Satar, Mehmet; Ozbarlas, Nazan; Uğuz, Aysun; Yapicioğlu, Hacer; Narli, Nejat; Bayram, Ibrahim (The Turkish Journal of Pediatrics, 2008)
Cardiac tumors are uncommon in neonates and most of them are histologically benign. The most common cardiac tumor in neonates and infants is rhabdomyoma. Malignant cardiac tumors are considerably rarer, and rhabdomyosarcoma (RMS) is the leading malignancy. To our knowledge, only one case of intrapericardial RMS was reported in the literature, in a seven-month-old baby. Here we present another newborn baby with intrapericardial RMS.